1969
DOI: 10.1139/f69-056
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Preliminary Characterization of Some Aeromonas salmonicida Bacteriophages

Abstract: Bacteriophages for Aeromonas salmonicida were isolated from water and mud samples taken from 13 of 19 trout hatcheries and ponds examined in southern Ontario. Nine of the 13 locations were known to have histories of furunculosis disease. The bacteriophages studied formed three serological groups and two distinct morphological types. Phages of serological groups I and II possessed similar morphology; those of group III resembled the coli T-even phages. All possessed complex symmetry consisting of a head and tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 2 publications
0
20
1
Order By: Relevance
“…The phages were propagated on L. garvieae NSS9310 (indicator bacterium) by the double agar-overlay method (Paterson et al 1969), and the susceptibilities of L. garvieae strains were then assessed by plaque formation using the same method.…”
Section: Methodsmentioning
confidence: 99%
“…The phages were propagated on L. garvieae NSS9310 (indicator bacterium) by the double agar-overlay method (Paterson et al 1969), and the susceptibilities of L. garvieae strains were then assessed by plaque formation using the same method.…”
Section: Methodsmentioning
confidence: 99%
“…After incubation at 37°C overnight, the culture was centrifuged at 4,500 xg for 10 min and the supernatant was filtered through a 0.22-μm-poresize membrane filter. The presence of a lytic phage in the filtrate was examined by using the double layer method with some modifications (Paterson et al, 1969). One hundred μl of the filtrate was mixed with 400 μl of a log phase culture of S. Typhi SSH1 and incubated at 37°C for 30 min.…”
Section: Bacteriophage Isolation and Purificationmentioning
confidence: 99%
“…These phages were propagated in L. garvieae strain No. 16 using a double-layer agar method (Paterson et al 1969). Briefly, a mixture of phage and bacteria was cultured in soft agar overlaid TSA at 25OC for 24 h. After centrifugation of the soft agar showing plaques, 102 to 103 plaque-forming units (PFU) plate-', the supernatant was filtered through a 0.45 pm membrane filter and the phage concentration was adjusted to 10' PFU ml-l.…”
Section: Methodsmentioning
confidence: 99%
“…Phages of some fish pathogenic bacteria, such as Aeromonas salmonicida (Paterson et al 1969, Rodgers et al 1981, A. hydrophila (Merino et al 1990), and Yersinia ruckeri (Stevenson & Airdrie 1984), have been reported but no attempts at phage control were made for bacterial infections in fish. Although 2 papers, Wu et al (1981) and Wu & Chao (1982), mentioned the applicability of phages for biological control of fish pathogens (A. hydrophila and Edwardsiella tarda), at present we have no reliable reference experiments for phage therapy or control in the field of fish pathology.…”
Section: Introductionmentioning
confidence: 99%